MATH SOLVE

3 months ago

Q:
# Determine g(x+a)−g(x) for the following function.g(x)=4x2−6x

Accepted Solution

A:

Answer:8ax + (4a²- 6a)Step-by-step explanation:g(x)=4x²−6xg(x+a)= 4(x+a)² - 6(x+a)= 4( x² + 2ax + a²) - 6x - 6a= 4x² + (4)2ax + (4)a² - 6x - 6a= 4x² + 8ax + 4a² - 6x - 6a= 4x² + 8ax - 6x + 4a²- 6a= 4x² + (8a - 6)x + (4a²- 6a)g(x+a) - g(x)= [4x² + (8a - 6)x + (4a²- 6a)] - (4x²−6x)= 4x² + (8a - 6)x + (4a²- 6a) - 4x² + 6x= (8a - 6)x + (4a²- 6a) + 6x= (8a - 6 + 6)x + (4a²- 6a)= 8ax + (4a²- 6a)